Searching for a relevant definition of sarcopenia: results from the cross‐sectional EPIDOS study. Issue 2 (27th April 2015) - Dupuy, Charlotte; Lauwers‐Cances, Valérie; Guyonnet, Sophie; Gentil, Catherine; Abellan Van Kan, Gabor; Beauchet, Olivier; Schott, Anne‐Marie; Vellas, Bruno; Rolland, Yves
Abstract: Background: The diversity of definitions proposed for sarcopenia has been rarely tested in the same population, and so far, their clinical utilities for predicting physical difficulties could not be clearly understood. Our objective is to report the prevalence of sarcopenia and the characteristics of sarcopenic community‐dwelling older women according to the different definitions of sarcopenia currently proposed. We also assessed these definitions for their incremental predictive value over currently standard predictors for some self‐reported difficulties in physical function and knee extension strength. Methods: Cross‐sectional analysis included data from 3025 non‐disabled women aged 75 years or older without previous history of hip fracture from the inclusion visit of the EPIDémiologie de l'OStéoporose study. A total body composition evaluation was available for 2725 women. Sarcopenia was defined using six different definitions of sarcopenia based on different muscle mass, gait speed, and grip strength cut‐offs. Self‐reported difficulties in physical function and knee extension strength were collected. Logistic regression and multiple linear regression models were built for each physical dysfunction, and the predictive capacity of sarcopenia (one model for each definition) was studied using the C‐statistic, the net reclassification index, or adjusted R 2 . Results: The estimated prevalence of sarcopenia ranged from 3.3–20.0%. Only 85 participants (3.1%) were identified having sarcopenia according to all definitions. All definitions were, to some degree, associated with self‐reported difficulties in physical function and knee extension strength, but none improved the predictive ability of the self‐reported difficulties in physical function. Conversely, all definitions accounted for a small but significant amount of explained variation for predicting knee extension strength. Conclusions: Prevalence of sarcopenia varies widely depending on the definition adopted. Based on this research, the current definitions for sarcopenia does not substantially increment the predictive value of clinical characteristics of patients to predict self‐reported physical difficulties and knee extension strength.